2016
DOI: 10.1016/j.jcis.2016.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Active targeting co-delivery system based on pH-sensitive methoxy-poly(ethylene glycol)2K-poly(ε-caprolactone)4K-poly(glutamic acid)1K for enhanced cancer therapy

Abstract: In this paper, we successfully synthesized folate-modified pH-sensitive copolymer methoxy-poly(ethylene glycol)2K-poly(ε-caprolactone)4K-poly(glutamic acid)1K (mPEG2K-PCL4K-PGA1K-FA), which could form the polymeric assembly in an aqueous solution, for co-delivering hydrophilic drugs doxorubicin hydrochloride (DOX) and verapamil hydrochloride (VER) (FA-poly(DOX+VER)). Since VER was an effective P-glycoprotein inhibitor, the combination of DOX and VER could reverse the multidrug resistance efficiently and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…As shown in Figure S6 (Supporting Information), the hemolysis ratio of HA/Ara‐IR820@ZIF‐8 was below 5% even at the highest concentration, indicating negligible red blood cells would be destroyed by this formulation. It had been reported that the hemolysis ratio below 10% could be acceptable in intravenous administration . Therefore, the low hemolytic toxicity of HA/Ara‐IR820@ZIF‐8 demonstrated that our formulation was suitable for intravenous administration.…”
Section: Resultsmentioning
confidence: 75%
“…As shown in Figure S6 (Supporting Information), the hemolysis ratio of HA/Ara‐IR820@ZIF‐8 was below 5% even at the highest concentration, indicating negligible red blood cells would be destroyed by this formulation. It had been reported that the hemolysis ratio below 10% could be acceptable in intravenous administration . Therefore, the low hemolytic toxicity of HA/Ara‐IR820@ZIF‐8 demonstrated that our formulation was suitable for intravenous administration.…”
Section: Resultsmentioning
confidence: 75%
“…23 In recent years, hollow mesoporous silica nanoparticles (HMSN) have emerged as an efficient tool for drug delivery because of their unique properties, such as large surface area, high pore volume, tunable pore size, and biocompatibility. In addition, they can be easily modified.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Many strategies aiming at effective reversal of MDR have been investigated through the co-delivery of chemotherapeutic agents and P-gp inhibitor by nanoparticles. 6,[12][13][14][15] For example, Wang et al 16 reported that polymeric micelles co-encapsulated with PTX and tacrolimus (a P-gp inhibitor) (P-F/M) could improve intracellular concentration of PTX and showed much stronger cytotoxicity against PTX-resistant human ovarian cancer A2780/PTX cells than PTX-loaded micelles. Unfortunately, the P-gp inhibitor actions in a concentration-dependent manner and the simultaneous release…”
Section: Introductionmentioning
confidence: 99%